ANALISIS PEMILIHAN PEMASOK HIJAU KOMODITI KAOLIN DENGAN MENGGUNAKAN INTEGRASI METODE BWM-PROMETHEE PADA PT.XYZ - Priyati Priyati; Suharjito Suharjito; Elisa Tanuwijaya (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
As the international community pays more and more attention to environmental issues, people tend to think about how to adapt to various issues in order to progress and develop in an environmentally conscious way in this era of globalization. The increasing demand for innovative and environmentally friendly products has prompted companies to focus on creating green supply chains, and companies adopt practices that minimize environmental damage (Rehman et al., 2015), which makes this a necessary condition to address competition in global markets Businesses innovate, select companies that meet the green supply chain standards for evaluation. This research aims to get the right criteria when selecting green kaolin suppliers in the supply chain and prioritise suppliers to find out which one is the best fit for the company.Method used in this study is the BWM method for weighting criteria and assessing the performance of green supply chain-based kaolin suppliers using the PROMETHEE method. This study compares the TOPSIS and Promethee methods in their ranking and the results show that the Promethee method has accuracy and correlation with ranking values ​​ (Beniyanto & P, 2018), and can be used for qualitative and quantitative data compared to TOPSIS, but TOPSIS has the advantage that the concept is simpler and easier understood so that decision-making is faster.